Myth A Symposium - Sebeok, Thomas A. (Indiana University Press, 1980)
Myth and Language explores the less universally accepted supposition that, particularly for the realm of literature, these two domains are necessarily interrelated. . . . Unlike previous studies of symbiosis, which have tended to neglect the importance of language, Myth and Language fully considers the influence of social context on the nature of literary language. Albert Cook begins his investigation into the relationship of myth and language with a critique of Levi-Strauss. . . .Another section traces the redefinition of the relationship of myth and language from the oral Greek culture of Homer to the development of the discrete forms of lyric poetry, philosophy, and historiography. A final section examines the necessary reliance of elementary literary forms-proverb, riddle, parable, metaphor-on the translation of mythic concerns into language. This book is a cogent argument for the dependence of literary expression on mythic formulations.